1978
DOI: 10.1126/science.202.4372.1045
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Impact of Airborne Effluents of Coal and Nuclear Plants

Abstract: Radiation doses from airborne effluents of model coal-fired and nuclear power plants (1000 megawatts electric) are compared. Assuming a 1 percent ash release to the atmosphere (Environmental Protection Agency regulation) and 1 part per million of uranium and 2 parts per million of thorium in the coal (approximately the U.S. average), population doses from the coal plant are typically higher than those from pressurized-water or boiling-water reactors that meet government regulations. Higher radionuclide content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(32 citation statements)
references
References 3 publications
0
29
1
2
Order By: Relevance
“…Use of this fuel has been associated with small radiation releases (McBride et al, 1978;Bauman & Howat, 1981) but there was no indication in this study that these two stations had an associated pattern of increasing cancer SMRs.…”
Section: Resultscontrasting
confidence: 42%
“…Use of this fuel has been associated with small radiation releases (McBride et al, 1978;Bauman & Howat, 1981) but there was no indication in this study that these two stations had an associated pattern of increasing cancer SMRs.…”
Section: Resultscontrasting
confidence: 42%
“…[26]. The concentrations of these radionuclides are usually low in the coal, when it is burnt in the boiler, the fly ash that is emitted through the stack to atmosphere gets enriched with some of the radionuclides and hence combustion of coal on a large scale for electricity generation becomes important from environmental point of view [27]. Earlier studies indicate that the radioactivity level of Indian fly ash is almost similar to that of normal soil and the radioactive level in lignite fly ash was found less than that of bituminous and sub-bituminous coal [13,28].…”
Section: Radioactivity Level Of Jarosite and Fly Ashmentioning
confidence: 99%
“…Thus, coal combustion is considered as one source of radioactive material in the environment [2][3][4][5]. Though it is controversial, the radiation doses from atmospheric emission of a coal-fired power plant were considered to be greater than those from a nuclear plant of comparable size [6,7]. In 1978, it was reported that as high as 2,975 kg uranium were emitted into the atmosphere from one Chinese coal-fired power plant [8].…”
Section: Introductionmentioning
confidence: 99%